1998
DOI: 10.1080/080352598750031635
|View full text |Cite
|
Sign up to set email alerts
|

"Idiopathic neutropenia" in very low birthweight infants

Abstract: We employed a standardized investigative approach to evaluate four cases of "idiopathic neutropenia" in very low birthweight infants. The evaluation included maternal anti-neutrophil antibodies, a marrow aspiration, and a three-day trial of recombinant granulocyte colony-stimulating factor (rG-CSF). All patients had neutropenia at or shortly following delivery, and remained neutropenic (generally <500/microl) for 1-9 weeks until rG-CSF was administered. Blood and bone marrow studies in all 4 indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…This interpretation is consistent with the reduced, but not depleted, marrow reserve we previously reported among four patients with this condition. 1 We observed that rG-CSF administration for 3 consecutive days effectuated a rapid and substantial increase in blood neutrophil counts that persisted for at least 5 days, but did not persist to 12 or to 15 days. We observed no clear benefit to rG-CSF administration among the five recipients, compared with the five placebo recipients, other than on blood neutrophil counts.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This interpretation is consistent with the reduced, but not depleted, marrow reserve we previously reported among four patients with this condition. 1 We observed that rG-CSF administration for 3 consecutive days effectuated a rapid and substantial increase in blood neutrophil counts that persisted for at least 5 days, but did not persist to 12 or to 15 days. We observed no clear benefit to rG-CSF administration among the five recipients, compared with the five placebo recipients, other than on blood neutrophil counts.…”
Section: Discussionmentioning
confidence: 67%
“…All responded to a 3-day course of recombinant granulocyte colonystimulating factor (rG-CSF) (10 mg/kg/day) with an increase in blood neutrophil counts. 1 Our investigations suggested that this variety was the result of reduced neutrophil production, which was not cyclic, not alloimmune, and not associated with recognized inborn errors, bacterial or viral infections, or medications.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations